MSME financial management strategies in increasing tax costs - Tri Widyana Anggraini; Anisah Zuhra Hasibuan; Heny Triastuti Kurnianingsih; Farida Khairani Lubis; Lusi Elviani (Proceeding International Conference on Accounting and Finance, 2024)
Financial management is very important in MSMEs. By understanding financial management, a person’s habits in managing finances will improve. Financial management is all financial activities related to planning and recording which aim to ensure business continuity, whether the business runs smoothly or not. MSMEs are very influential in tax costs, having tax costs can be one step to prevent the economic and financial crisis of the Indonesian economy. The aim of this research is to find out how MSMEs have a big influence on tax costs and how MSMEs are managed in Indonesia. In this research we used 26 financial management, MSME and tax costs journals that we had read. In order to produce accurate data, we have reviewed previous journals. The results of this research show that MSMEs really understand financial management, and the amount of tax costs that must be incurred in carrying out taxation really determines the level of taxpayer compliance in MSMEs.